2017
DOI: 10.5539/ijbm.v12n4p67
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality and Customer Satisfaction in the Electronic Banking

Abstract: The present study aims to assess the degree of service quality and customer satisfaction in the electronic banking context in Battticaloa district. To achieve these objectives a questionnaire was developed with item measures that capture the service quality and customer satisfaction constructs. In a study of 231 respondents (51 percent of response rate), unidimensionality, reliability and validity assessments were conducted to validate the key constructs and one sample t-test was performed to test the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 82 publications
2
15
1
4
Order By: Relevance
“…In addition, construct validity is assessed through convergent and discriminant validity. As consistent with the past studies, this study used construct reliability and average variance extracted to assess the convergent validity (Tharanikaran, Sritharan & Thusyanthy 2017cite Choi, Huang, Jeffrey & Baek, 2013and Wei & Lu, 2013. Accordingly, the construct reliability for all dimensions, exceed the benchmark of 0.70 (Fornell & Larcker, 1981), whilst average variance extracted exceed the threshold value of 0.50 (Hair et al, 1998) indicated that they had acceptable levels of convergent validity (see Table 7).…”
Section: Reliability and Validitymentioning
confidence: 99%
“…In addition, construct validity is assessed through convergent and discriminant validity. As consistent with the past studies, this study used construct reliability and average variance extracted to assess the convergent validity (Tharanikaran, Sritharan & Thusyanthy 2017cite Choi, Huang, Jeffrey & Baek, 2013and Wei & Lu, 2013. Accordingly, the construct reliability for all dimensions, exceed the benchmark of 0.70 (Fornell & Larcker, 1981), whilst average variance extracted exceed the threshold value of 0.50 (Hair et al, 1998) indicated that they had acceptable levels of convergent validity (see Table 7).…”
Section: Reliability and Validitymentioning
confidence: 99%
“…As consistent with past studies, this study also used Construct Reliability (CR) and Average Variance Extracted (AVE) to assess the convergent validity (Zdravkovic, Magnusson & Stanle, 2010). Accordingly, CR and AVE for all dimensions were well above the recommended levels of 0.7 (Tharanikaran, Sritharan & Thusyanthy 2017cite Fornell & Larcker, 1981 and 0.5 (Tharanikaran, Sritharan & Thusyanthy 2017cite Hair, Anderson, Tatham & Black, 1998, respectively, providing strong evidence of convergent validity (see Table 2). …”
Section: Unidimensionality Reliability and Validity Assessmentmentioning
confidence: 94%
“…(Kurniawan, 2016) mengamati, "Pembeli persepsi nilai merupakan trade off antara kualitas atau manfaat yang mereka anggap dalam produk terhadap pengorbanan yang mereka anggap dengan membayar harga". Dalam memaksimalkan nilai yang dirasakan pelanggan perusahaan harus mampu meningkatkan nilai yang dirasakan pelanggan, misalnya meningkatkan kualitas atau mengurangi pengorbanan mereka dengan cara memberikan diskon/mengurangi harga yang dibayarkan, mengurangi waktu dan usaha untuk membeli (Tharanikaran et al, 2017).…”
Section: Tabel 1 Perbandingan Tas Merk Palomino Pada Zalora Dan Centunclassified